Pengaruh Pemberian Kacang Hijau (Phaseolus radiatus) Terhadap Peningkatan Kadar Hemoglobin Tikus Putih (Rattus norvegicus) Jantan Galur Wistar - Nora Maulina; Indra Pehulisa Sitepu (Jurnal Pendidikan Kimia (JPKim), 2015)
Abstract. Mung beans (Phaseolus radiates) are a kind of legume which green  round and oval. Mung beans contain substances that are required for the formation of blood cells so as to overcome the effects of decrease Hb. Mung beans can function on formation red blood cells contain substances that are needed by the body for the maturation and formation of blood cells and prevent anemia because phytochemical substances on mung beans very complete so it can help the process of hematopoiesis. The purpose of the research is to explore effect of mung beans to increase Hb of rats (Rattus norvegicus). This research used 27 male white rats species Rattus norvegicus strain wistar. Male white rats were divided into 3 groups, 1 control group and 2 treatment groups. Control group was given aqua ad libitum for 7 days, Treatment group was given mung beans with gradual dose of 18 and 36 gr/kgBB/day. The result of data analysis with Kruskal Wallis test showed a P value 0,003 (p < 0,05), thus obtained significant differences in mean Hb levels after given mung beans. The result showed that giving mung beans affect the increase in Hb concentration white male rats. Keywords : Hb, mung beans, rats